Alquimias do analógico e do digital: máquinas e práticas audiovisuais do passado e do presente - Menezes, Natália Aly (2017)
This research seeks to contextualize the experimental audiovisual practices of the present through a strong connection with the past. Thus, the thesis excavates the earliest sources of optical and acoustic investigations that have, over the years, resulted in machines and media that surround us nowadays. However, the research does not follow linearities of traditional history. The theoretical methodology of the media archaeology is used seeking to restructures the mediatic historicism. Therefore, it’s possible to make analogies between alchemical practices (methods and discoveries), and the audiovisual contemporary practices. Moreover, this research aims to approach past and present in a technical way, in the union and combination of analog and digital, proposing an analysis and the creation of fruitful hybrid structures of the experimental audiovisual